Supporting Preschool Children’s STEM Learning with Parent-Involved Early Engineering Education - Ata-Aktürk, Aysun; Demircan, H. Özlen (Springer Science and Business Media LLC, 2020)
This study examines the development of a STEM-based (Science, Technology, Engineering, and Mathematics) and parent-involved engineering design curriculum for early childhood education and investigates its design principles and contributions to children’s STEM-related learning. This research utilized a design-based research methodology broken into three main phases (preliminary research, prototyping, and assessment). The data were gathered over a 2-year span, and the curriculum was designed and revised during the prototyping phase’s three iterative cycles. This paper presents the findings of a field test that involved two early childhood education teachers, five preschool children, and five parents. Findings validated eight key design principles of the curriculum and revealed that the curriculum contributes to the knowledge, skills, feelings, and dispositions children have towards STEM. The findings suggest that the developed curriculum can be used as a novel way of integrating STEM into early childhood education, with a particular focus on engineering, while encouraging parental involvement.
Keywords: 4. Education